The West Wing - Season 7 Episodes 1-22 - Misiano, Christopher; Graves, Alex; Bernstein, Andrew; Alda, Alan; Channing, Stockard; Smits, Jimmy (Warner, 2006)
"The West Wing" revolves around the trials of the Bartlet administration, giving viewers a glimpse into presidential politics in the United States, with interesting characters whose humor and dedication touch our hearts. [www.tvtome.com]
Keywords: DVD-Video